The contribution of The Public Organization "Service to Poland" to the development of physical culture in Western Pomerania in the years 1948-1955 - Ryszard Stefanik; Maciej Zawadzki (Jan Długosz University in Częstochowa, 2020)
In 1948 The Public Organization "Service to Poland" (Powszechna Organizacja "Służba Polsce": PO "SP") was established which aimed at using youths to rebuild the country, their military training and indoctrination. The future of socialistic country. dependent on Soviet Union was mainly depending on the right degree of society obedience and effective work for development of state economy. Significant role in this process was played by PO "SP", which was supposed to cover entire Polish youths aged 16 to 21. The improvement of combat skills was realized in the form of physical education and sport competition, which in time became an important element of organization life. This activity has gained special meaning in the rural parts of country. Creating circles of Folk Sports Teams (LZS) was helped, sport - shooting competitions, sport Sundays and LZS Spartakida's were organized. The research involved analysis of archival and press materials as well as literature on the subject applying the inductive method. Furthermore, conclusions were drawn without the possibility of direct access to relevant materials, as well as based on knowledge beyond the source (the method of deduction).